2004
DOI: 10.3928/1542-8877-20040301-17
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Photodynamic Therapy in Choroidal Neovascularization Complicating Idiopathic Central Serous Chorioretinopathy

Abstract: Abstract. Two consecutive patients with idiopathic central serous chorioretinopathy and decreased vision subsequent to subfoveal choroidal neovascular membranes were treated with photodynamic therapy applied using the protocol of the Treatment of AgeRelated Macular Degeneration with Photodynamic Therapy Study Group. Main outcome measures included best-corrected visual acuity, biomicroscopic appearance, and leakage on fluorescein and indocyanine green angiography. Photodynamic therapy offered anatomical, angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Resolution of serous detachment followed treatment in the majority of patients, as did visual improvement. No complications have been reported (Canakis et al. 2003, 2004; Cardillo et al.…”
Section: Treatmentmentioning
confidence: 99%
“…Resolution of serous detachment followed treatment in the majority of patients, as did visual improvement. No complications have been reported (Canakis et al. 2003, 2004; Cardillo et al.…”
Section: Treatmentmentioning
confidence: 99%
“…8,11,12,15 Occult (subretinal pigment epithelium [RPE], Type 1 neovascularization) CNV secondary to CSC has rarely been described before. 4,7 In this report, we describe the clinical and multimodal imaging features of patients with Type 1 neovascularization that we believe occurred secondary to long-standing CSC.…”
mentioning
confidence: 95%
“…Spaide et al 4 examined a consecutive series of 130 patients with CSC over an 18-month period and detected 12 patients (9%) who had CNV. Other studies have focused on treatment of a few patients with CNV secondary to CSC treated with intravitreal anti-vascular endothelial growth factor (VEGF), 5,6 photodynamic therapy (PDT), [7][8][9][10][11] or submacular surgery. 12 Not all studies found an association.…”
mentioning
confidence: 99%
“…1,2,5,6 Chronic CSC may predispose to the development of choroidal neovascularization (CNV). [7][8][9][10][11][12][13][14][15][16][17] The prevalence of CNV in chronic CSC cases has been estimated by different authors to be around 4% to 8%. 1,8,9 Long-standing CSC can show subtle signs that may suggest the presence of an occult CNV such as an indistinct late leakage on fluorescein angiography (FA) or the presence of fibrin or lipid deposition, as well as the presence of PED.…”
mentioning
confidence: 99%